Leucine supplementation via drinking water reduces atherosclerotic lesions in apoE null mice - Zhao, Yang; Dai, Xiao-yan; Zhou, Zhou; Zhao, Ge-xin; Wang, Xian; Xu, Ming-jiang (Acta pharmacologica Sinica, 2016)
Aim： Recent evidence suggests that the essential amino acid leucine may be involved in systemic cholesterol metabolism. In this study, we investigated the effects of leucine supplementation on the development of atherosclerosis in apoE null mice. Methods： ApoE null mice were fed with chow supplemented with leucine （1.5% w/v） in drinking water for 8 week. Aortic atherosclerotic lesions were examined using Oil Red 0 staining. Plasma lipoprotein-cholesterol levels were measured with fast protein liquid chroma- tography. Hepatic gene expression was detected using real-time PCR and Western blot analyses. Results： Leucine supplementation resulted in 57.6% reduction of aortic atherosclerotic lesion area in apoE null mice, accompanied by 41.2% decrease of serum LDL-C levels and 40.2% increase of serum HDL-C levels. The body weight, food intake and blood glucose level were not affected by leucine supplementation. Furthermore, leucine supplementation increased the expression of Abcg5 and Abcg8 （that were involved in hepatic cholesterol efflux） by 1.28- and 0.86-fold, respectively, and significantly increased their protein levels. Leucine supplementation also increased the expression of Srebfl, Scdl and Pgclb （that were involved in hepatic triglyceride metabolism） by 3.73-, 1.35- and 1.71-fold, respectively. Consequently, leucine supplementation resulted in 51.77% reduction of liver cholesterol content and 2.2-fold increase of liver triglyceride content. Additionally, leucine supplementation did not affect the serum levels of IL-6, IFN-γ, TNF-α, IL-10 and IL-12, but markedly decreased the serum level of MCP-1. Conclusion： Leucine supplementation effectively attenuates atherosclerosis in apoE null mice by improving the plasma lipid profile and reducing systemic inflammation.